Lembaga Pendidikan Pesantren: Jaringan dan Pertumbuhan Komunitas Islam - Bakri, Naharuddin; Rama, Bahaking; Rusmin B, Muhammad (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study aims to determine the Islamic Boarding School Educational Institution (Islamic Community Network and Growth). Given the role of Islamic boarding schools is very large in the world of education, especially in Islamic education. To produce the next generation who are intelligent and have noble morals, comprehensive education is needed. This study is the result of a study or literature review sourced from Library literature or Library materials, both in the form of books and in the form of articles published through printed and online scientific journals. The focus of the study in this article is on Islamic Boarding School Educational Institutions that are relevant to Islamic religious education learning. The data obtained are reviewed/analyzed and then presented descriptively in the form of an article. The results of the study show that Islamic Boarding School Educational Institutions have developed and are found in several areas visited by Islam and some have come late with this being considered successful in establishing and developing Islamic boarding schools in the true sense is Raden Rahmat (Sunan Ampel). He founded an Islamic boarding school in Kembang Kuning which then moved to Ampel Denta (Surabaya). The conclusion is that Islamic Boarding Schools are one of the oldest educational institutions in Indonesia. As the oldest institution, Islamic boarding schools have contributed to coloring the journey of the history of this nation. This contribution is not only related to the educational aspect alone, but also related to other fields on a wider scale.